A REVIEW OF COCONUT RESEARCH & DEVELOPMENT - Hugh C. Harries (International Coconut Community, 1999)
By looking at the titles of articles published in CORD since it began, in 1985, it should be possible to assess what areas of coconut research and development are important. This is so, because CORD is intended for a select group of readers - those who know about coconuts. The writers of articles for CORD, unlike authors of articles in specialist scientific or economic journals, do not have to compete for space with reports on the cutting-edge of science or with predictions about world-market economic forces. Which is a pity, because if they did it would mean that coconut was back in the position of the world's leading source of vegetable oil that it held for half a century. There are other technical and scientific journals, as well as national language publications, to which coconut R&D specialist can, and do, submit articles, but CORD is the one location where both the writer and the reader should be on the same wavelength.